Nutrient regulation of insulin secretion and action - Newsholme, Philip; Cruzat, Vinicius; Arfuso, Frank; Keane, Kevin (BioScientifica, 2014)
Pancreatic ß-cell function is of critical importance in the regulation of fuel homoeostasis, and metabolic dysregulation is a hallmark of diabetes mellitus (DM). The ß-cell is an intricately designed cell type that couples metabolism of dietary sources of carbohydrates, amino acids and lipids to insulin secretory mechanisms, such that insulin release occurs at appropriate times to ensure efficient nutrient uptake and storage by target tissues. However, chronic exposure to high nutrient concentrations results in altered metabolism that impacts negatively on insulin exocytosis, insulin action and may ultimately lead to development of DM. Reduced action of insulin in target tissues is associated with impairment of insulin signalling and contributes to insulin resistance (IR), a condition often associated with obesity and a major risk factor for DM. The altered metabolism of nutrients by insulin-sensitive target tissues (muscle, adipose tissue and liver) can result in high circulating levels of glucose and various lipids, which further impact on pancreatic ß-cell function, IR and progression of the metabolic syndrome. Here, we have considered the role played by the major nutrient groups, carbohydrates, amino acids and lipids, in mediating ß-cell insulin secretion, while also exploring the interplay between amino acids and insulin action in muscle. We also focus on the effects of altered lipid metabolism in adipose tissue and liver resulting from activation of inflammatory processes commonly observed in DM pathophysiology. The aim of this review is to describe commonalities and differences in metabolism related to insulin secretion and action, pertinent to the development of DM.